Does CPAP Affect Patient‐Reported Voice Outcomes?. (16th January 2018) - Hartke, Vance; Gillespie, Amanda; Smith, Libby J.; Soose, Ryan J.
Abstract : Upper aerodigestive tract symptoms are common in patients with obstructive sleep apnea (OSA). It remains unclear whether continuous positive airway pressure (CPAP) improves or worsens these otolaryngology symptoms. As therapy‐related side effects limit CPAP adherence, this study aimed to determine if CPAP negatively affects voice, sinonasal, and reflux symptoms of the upper airway. Case series with planned data collection was performed at an academic otolaryngology sleep center. Newly diagnosed patients with OSA were evaluated before and 6 months after initiating CPAP therapy. Data collected included CPAP data download, Reflux Symptom Index (RSI), Epworth Sleepiness Scale (ESS), Voice Handicap Index 10 (VHI‐10), Sino‐Nasal Questionnaire (SNQ), and oral dryness visual analog scale (VAS). For the 11 CPAP‐adherent participants, the RSI significantly improved with CPAP (mean RSI, 22.0‐9.5; P =. 002); however, the VAS, VHI‐10, and SNQ did not change after 6 months of CPAP therapy. In a small sample size, patient‐reported voice outcomes (VHI‐10) and other upper aerodigestive tract symptoms did not worsen with CPAP; rather, CPAP therapy was associated with a reduction in reflux symptoms.